2010
DOI: 10.3892/ijo_00000843
|View full text |Cite
|
Sign up to set email alerts
|

Patient surveillance after treatment for soft-tissue sarcoma

Abstract: Abstract. About 1% of all cancers are soft tissue sarcomas (STS); about 60% of these occur in the extremities. Posttreatment surveillance programs are designed to identify recurrence, new primary cancers, and complications of therapy early enough to increase survival duration and quality of life. The intensity of surveillance varies among surgeons. We hypothesized that geographic factors would account for much of this variation. The 1,592 members of the Society of Surgical Oncology were surveyed regarding thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…A separate analysis of the survey data showed little impact on surveillance strategy with surgeon age and experience; the only difference was more frequent use of erythrocyte sedimentation rate, extremity X‐rays and bone scans among the older surgeons . Several years later, another analysis of the survey data was done which found little to no variation in surveillance strategies by US metropolitan and geographic areas or level of managed care organization penetration .…”
Section: Perceptions Of Surveillance Strategies and Actual Practicementioning
confidence: 98%
“…A separate analysis of the survey data showed little impact on surveillance strategy with surgeon age and experience; the only difference was more frequent use of erythrocyte sedimentation rate, extremity X‐rays and bone scans among the older surgeons . Several years later, another analysis of the survey data was done which found little to no variation in surveillance strategies by US metropolitan and geographic areas or level of managed care organization penetration .…”
Section: Perceptions Of Surveillance Strategies and Actual Practicementioning
confidence: 98%
“…Recent published studies have revealed a yearly incidence of about 4-5/100,000 in Europe; liposarcoma and leiomyosarcoma are the most common histological subtypes (15-17). Nearly every third patient with primarily local STS will develop DM during the follow-up period, most likely in the lungs (18).The large majority of STS are primarily located in the extremities; about 40% occur in the lower limbs (1,2,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The second most frequent location is the abdomen (retroperitoneal or visceral); the lesions are usually very voluminous at the time of presentation (1,(19)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…The large majority of STS are primarily located in the extremities; about 40% occur in the lower limbs (1,2,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The second most frequent location is the abdomen (retroperitoneal or visceral); the lesions are usually very voluminous at the time of presentation (1,(19)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…However, the ideal postoperative protocol, particularly the frequency of followup and appropriate screening modalities for these uncommon neoplasms, remains ill defined [8,10,18]. Current guidelines are not based on high-quality evidence [10,18]. Current postoperative surveillance regimes are empirical and vary widely from center to center [8,9,18].…”
Section: Introductionmentioning
confidence: 99%
“…With improved patient survival, followup surveillance strategies are becoming increasingly important with considerable clinical and fiscal implications. However, the ideal postoperative protocol, particularly the frequency of followup and appropriate screening modalities for these uncommon neoplasms, remains ill defined [8,10,18]. Current guidelines are not based on high-quality evidence [10,18].…”
Section: Introductionmentioning
confidence: 99%